A study on the dynamic instability of CFST arches with spatial curvature differences. (April 2023) - Xie, Kaizhong; Guo, Xiao; Liang, Dong; Qin, Yue; Wei, Yong; Zhou, Yiming; Elchalakani, Mohamed
Highlights: Based on the change of fiber strain, the dynamic instability criterion of CFST arch space curvature difference is proposed. The accuracy of the critical curvature difference of instability failure is verified by the comparison with instability failure tests. The proposed critical curvature difference can accurately assess the dynamic stability of CFST arch structure. Abstract: With the rapid development of the construction technology of concrete-filled steel tube (CFST) arch bridges, the width-span and width-to-height ratios continue to increase, which cause stability problems, especially for the dynamic stability. The current Budiansky-Roth criterion (B-R criterion) and the energy criterion are hard to use and cannot be quantitatively described. Therefore, a CFST arch dynamic instability criterion by the difference in spatial curvature based on the changes in fiber strains is proposed in this paper. Firstly, the critical spatial curvature difference is derived based on the structural characteristics of CFST arches and is the threshold value of the dynamic stability discrimination. Then, the calculation format of the CFST arches' dynamic instability criterion is established by the central difference method, and the calculation procedure is programmed. Furtherly, the accuracy of the proposed critical curvature difference method is validated by the instability-induced failure experiments. In addition, the discrimination results of instability-induced failure experiments are also obtained by B-R criterion as well as the energy criterion. The discrimination result of the proposed critical curvature difference method is consistent with those of B-R criterion and energy criterion. Moreover, the method proposed quantifies the critical load of dynamic instability into the threshold index by the critical curvature difference and has easy-to-measure parameters as well as easy to operate, which are more suitable for the engineering applications compared with other methods.